Center-Pivot-Irrigated Sunflowers Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2001)
The cost-return projection estimates the cost of producing center-pivot-irrigated sunflowers in Kansas.
MF800_2001_10
Keywords: MF800; Economics; Crops; MF